Solution:
Given the equation;
![x^2+2x-1=0](https://img.qammunity.org/2023/formulas/mathematics/college/l0p4iltzgduesfkhs4icurkk2igpl4quwa.png)
Using completing the square method; take one to the other side of the equation and change the sign.
![x^2+2x=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/rqw4t8iywl7bes2gxjcggaxpt71kvoq9z1.png)
Add the square of half of the coefficient of x to both sides of the equation;
![\begin{gathered} x^2+2x+((1)/(2)(2))^2=1+((1)/(2)(2))^2 \\ \\ x^2+2x+1=1+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ih5dyk6757wp0z9rb1hg8ksezkn25idyux.png)
Factorize the left side and simplify the right side;
![(x+1)^2=2](https://img.qammunity.org/2023/formulas/mathematics/college/efndco45mecqukqr8omavsbxz2l97shiz1.png)
Thus, the form is;
![(x+1)^(2)=2](https://img.qammunity.org/2023/formulas/mathematics/college/wzm8rqhgz16mc501rac9wpxb4wf3gfa2qv.png)
And the solution is;
![\begin{gathered} x=-1\pm√(2) \\ \\ x=-1+√(2),x=-1-√(2) \\ \\ x=0.41,x=-2.41 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vad5nrqhs8hlikotgy13wm3lteuz4cre90.png)